2015
DOI: 10.1287/opre.2015.1392
|View full text |Cite
|
Sign up to set email alerts
|

K-Adaptability in Two-Stage Robust Binary Programming

Abstract: We propose to approximate two-stage distributionally robust programs with binary recourse decisions by their associated K-adaptability problems, which pre-select K candidate secondstage policies here-and-now and implement the best of these policies once the uncertain parameters have been observed. We analyze the approximation quality and the computational complexity of the K-adaptability problem, and we derive explicit mixed-integer linear programming reformulations. We also provide efficient procedures for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 55 publications
4
128
0
Order By: Relevance
“…It is illustrative to consider the size of the adaptable formulation at each iteration for the methods proposed in this paper versus the approach in Hanasusanto et al (2014). Their approach uses O (KN ) binary variables and O (2 K KN ) continuous variables where K is the number of partitions (selected a priori), with fractionality-inducing "big-M" constraints.…”
Section: Capital Budgetingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is illustrative to consider the size of the adaptable formulation at each iteration for the methods proposed in this paper versus the approach in Hanasusanto et al (2014). Their approach uses O (KN ) binary variables and O (2 K KN ) continuous variables where K is the number of partitions (selected a priori), with fractionality-inducing "big-M" constraints.…”
Section: Capital Budgetingmentioning
confidence: 99%
“…To compare our results with Hanasusanto et al (2014) we measured performance our method by the same metric: the improvement in objective relative to the solution with no adaptability, We add a new metric, gap, which estimates how far we are from the fully adaptive solution using the bound presented in Section 4.1,…”
Section: Capital Budgetingmentioning
confidence: 99%
“…For classical two-stage robust binary programs, it has been shown that the approximation provided by the Kadaptability formulation is tight whenever K exceeds the affine dimension of either the uncertainty set or the second-stage feasible region, see [6,Theorem 1]. We now show that this favorable approximation behavior generalizes to distributionally robust two-stage binary programs.…”
Section: The K-adaptability Problem With Objective Uncertaintymentioning
confidence: 55%
“…The assertion now follows if we replace the sets Ξ( ) with their inner approximations Ξ ( ), ∈ L, and reformulate the constraints as in [6,Theorem 5].…”
Section: B Omitted Proofsmentioning
confidence: 99%
See 1 more Smart Citation